Peran Suami dalam Penurunan Kecemasan Ibu Hamil Trimester III di Indonesia: Literature Review - Gian Wirabakti; Eka Afdi Septiyono (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: This study aimed to determined the influence of the husband's role on the level of anxiety of pregnant women in the III trimester in the face of childbirth. Method: This type of study used was the Traditional Literature Review. This type of design is a review that usually adopts a critical approach, such as assessing the theory or hypothesis of the previous researcher, examining the methods and results of a single primary study with an emphasis on background and contextual materials, not using a scientific method approach (depending on the wishes of the researcher) so that it can contain biases, cannot be replicated because the synthesis is carried out narratively. Result: The results of this study show that there is an influence of husband support on wives who experience anxiety in the third trimester of pregnancy where the group of pregnant women who do not live with their husbands has a high-moderate anxiety category compared to third trimester pregnant women who live with their husbands on average fall into the category of medium-low anxiety. had a moderate level of anxiety of 12 people (40%) and 18 people (60%) had a low level of anxiety. High anxiety levels of 19 people (63%) and 11 people (37%) had moderate levels of anxiety. Implication: It is hoped that it can be a reference to the husband that the importance of the husband's role in reducing the anxiety of pregnant women in childbirth. It is recommended to the husband to provide support and support to the mother in order to reduce the anxiety of the third trimester pregnant woman so that the delivery that will be faced can run well